2017
DOI: 10.1007/s10522-017-9710-z
|View full text |Cite
|
Sign up to set email alerts
|

Lipid (per) oxidation in mitochondria: an emerging target in the ageing process?

Abstract: Lipids are essential for physiological processes such as maintaining membrane integrity, providing a source of energy and acting as signalling molecules to control processes including cell proliferation, metabolism, inflammation and apoptosis. Disruption of lipid homeostasis can promote pathological changes that contribute towards biological ageing and age-related diseases. Several age-related diseases have been associated with altered lipid metabolism and an elevation in highly damaging lipid peroxidation pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
99
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(114 citation statements)
references
References 175 publications
0
99
0
Order By: Relevance
“…UDCA has confirmed that it can stabilize mitochondrial membrane potential . Mitochondria are unique organelles with a bilayer membrane, and their function depends on the coordination of proteins and lipids . PC, PE, and CL, acting as the main lipid molecules in the mitochondrial membrane, maintain the mitochondrial membrane integrity, and regulate proteins on the mitochondrial membrane.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…UDCA has confirmed that it can stabilize mitochondrial membrane potential . Mitochondria are unique organelles with a bilayer membrane, and their function depends on the coordination of proteins and lipids . PC, PE, and CL, acting as the main lipid molecules in the mitochondrial membrane, maintain the mitochondrial membrane integrity, and regulate proteins on the mitochondrial membrane.…”
Section: Discussionmentioning
confidence: 95%
“…The main phospholipids in the mitochondrial membrane are phosphatidylcholine (PC), phosphatidylethanolamine (PE), and cardiolipin (CL), which account for approximately 40%, 30%, and 15% of the total lipids, respectively . Changes in mitochondrial membrane phospholipid levels may have profound physiological and physical effects on the activity of key transmembrane proteins, such as respiratory chain proteins, and can cause mitochondrial dysfunction, resulting in cell apoptosis . Therefore, mitochondrial quality control mediated by regulating mitochondrial lipid metabolism may have great therapeutic potential in mitochondria‐related diseases …”
Section: Introductionmentioning
confidence: 99%
“…Whilst not the focus of the study, the authors speculate that MDA-modified vimentin may serve as an "eat me" signal leading to phagocytosis by macrophages ( Figure 2). Senescent cells commonly display higher levels of ROS, likely owing to changes in cell metabolism and/or the presence of dysfunctional mitochondria, which can lead to the oxidation of phospholipids (Ademowo et al, 2017). During apoptosis, oxidatively modified lipids on the surface of cell membranes can function as pattern recognition ligands promoting macrophage recognition and phagocytosis via the scavenger receptor CD36 (Hazen, 2008), RAGE (Friggeri et al, 2011) and other class I and class II scavenger receptors (Canton et al, 2013).…”
Section: Recognition Of Senescent Cells By Macrophages: Possible Mechmentioning
confidence: 99%
“…The positive charge carried by the triphenylphosphonium component enables MitoTEMPO to pass through the lipid bilayer into the mitochondrial matrix, where it accumulates to a concentration 1000-fold higher than in other areas [23]. Mitochondria consume as much as approximately 85% of the total amount of oxygen required by the cell to produce adenosine triphosphate, at the same time producing large amounts of reactive oxygen species (ROS) and lipid oxidation products [24]. As the TEMPO component of MitoTEMPO scavenges ROS such as superoxide dismutase, it can improve the status of many mitochondrion-associated diseases [23].…”
Section: Introductionmentioning
confidence: 99%